Economic Valuation of Mangrove Ecosystem in Sari Ringgung, Pesawaran Regency, Lampung Province - Efendi, Eko; Lahay, Almira Fardani; Susanti, Oktora (Faculty of Fisheries and Marine Science, Brawijaya University, 2024)
Mangrove ecosystems play an important role in human life. It’s ecological role includes trapping sediment, protecting shorelines, and providing a natural habitat. The economic function of mangrove forests is for it to be a place for mangrove ecotourism, source of fisheries, source of food, and so on. This research aimed to quantify the monetary value of mangrove forests in Sari Ringgung. The method used in this study is an exploratory descriptive method that quantifies the total value of direct and indirect use of mangrove forest ecosystems. The research results showed that the mangroves found mainly consisted of 5 types i.e. Avicennia marina, Rhizophora apculata, Rhizophora mucronata, Rhizophora stylos, and Bruguiera cylindrica. The total economic value of mangrove forests in the Sari Ringgung area, Pesawaran Regency is IDR 109,953,256,105, which consists of the use value ofIDR 46,855,529,425 and the non-use value of IDR 888,172,548. The use value consists of a direct use value of IDR 138,060,000 and an indirect use value of 46,717,469,425, while the non-use value consists of an existence value of 874,366,548, an option value of 62,209,554,132 and a value of 13,806,000. The total economic value of the mangrove forests was in the high-value category, although the area of mangrove forests in Sari Ringgung and Pesawaran Regency has decreased.